2020
DOI: 10.1044/2020_ajslp-19-00064
|View full text |Cite
|
Sign up to set email alerts
|

“Tell Me About Your Child”: A Grounded Theory Study of Mothers' Understanding of Language Disorder

Abstract: Purpose The purpose of this study was to generate a theory grounded in data explaining caregivers' understanding of their child's language disorder and the perceived role of speech-language pathologists in facilitating this knowledge. Method This study employed grounded theory as a conceptual framework. Qualitative data were generated based on semistructured interviews conducted with 12 mothers of children who had received speech-language pathology serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 50 publications
1
18
1
Order By: Relevance
“…Recent research suggests that barriers do exist. In extensive interviews with mothers of children who have DLD, it is clear that SLPs in school settings often give parents vague labels (e.g., language problem), irrelevant labels (e.g., speech problem), or no diagnostic label at all (Ash et al, 2020). Not surprisingly, the parents are confused.…”
Section: Reason 4: Educational Culture Constrains the Diagnosis Of Dldmentioning
confidence: 99%
“…Recent research suggests that barriers do exist. In extensive interviews with mothers of children who have DLD, it is clear that SLPs in school settings often give parents vague labels (e.g., language problem), irrelevant labels (e.g., speech problem), or no diagnostic label at all (Ash et al, 2020). Not surprisingly, the parents are confused.…”
Section: Reason 4: Educational Culture Constrains the Diagnosis Of Dldmentioning
confidence: 99%
“…For example, Archibald et al (2019) reported that many Canadian speech-language therapists do not provide a label for a child's language disorder when sharing findings with the parents. Ash et al (2020) reported that some U.S. mothers reported receiving confusing and irrelevant diagnostic terms for language disorder. Furthermore, in parental interviews conducted by Roulstone and Lindsay (2012), none of the parents used a diagnostic label in relation to the child's communication impairment but used other labels, such as attention-deficit/hyperactivity disorder, Asperger's, or dyslexia, when referring to their children's needs.…”
Section: Discussionmentioning
confidence: 99%
“…Improved understanding of parental views and experiences are important because they inform intervention and policy and enhance outcomes. Much of the research on parental perspectives has been conducted in English-speaking countries (i.e., Ash et al, 2020;Carroll, 2010;Davies et al 2016;Lyons et al, 2010;Roulstone et al, 2016). In the United Kingdom, Roulstone and Lindsay (2012) found that the desired outcomes of parents for their children with speech, language, and communication needs were social acceptance and independence, rather than outcomes specifically related to their children's communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although these labels are generally accepted by researchers and practitioners, they are still not well known compared with other neurodevelopmental conditions like ADHD, autism spectrum disorder or dyslexia. There is evidence to suggest that even parents of children with language disorders may not be given or may not use these labels (Ash, Christopulos, & Redmond, 2020). A further challenge relates to the cut-off points used to define language disorders and determine eligibility for service provision.…”
mentioning
confidence: 99%